Kesehatan Reproduksi Perempuan Rimba: Studi Tentang Kearifan Lokal Perempuan Rimba dalam Memanfaatkan Lingkungan - Zarfina Yenti (Kafa`ah: Journal of Gender Studies, 2017)
The aim of this research is to explore how the women of Orang Rimba keep their reproduction system healthy without the help of modern amenities. A qualitative research method was used in this study ehere the data taken from interviews, observation, and documentations. After several interviews, observation and by looking at the documentation, the researcher found that the women of Rimba people uses local wisdom in keeping their reproduction healthy, that is they use natural surroundings in their life in every way, including in keeping their reproduction system healthy. For example during menstruation circle, the women uses special tree bark as a substitute for ordinary sanitary napkins; during their pregnancy; they eat special fruit usually fruit with high acidity that they could found in the forest; they also uses natural way in preventing pregnancy; they also uses several natural plant to prevent pregnancy, such as the women eat turmeric plant and several other plants. During the birthing time, they have special place called “tanoh peranaan” where the women gives birth and no men even their husbands are not allowed to come. But even without modern amenities, these women have good reproduction system. The researcher also found that there are several things that Orang Rimba women do that almost similar with Islamic life, for example they wean their babies until they are two years old and this was also used to prevent pregnancies.